Analysis of medical service use of knee osteoarthritis and knee meniscal and ligament injuries in Korea: a cross-sectional study of national patient sample data - Chang Yong Suh; Yoon Jae Lee; Joon-Shik Shin; Jinho Lee; Me-riong Kim; Wonil Koh; Yun-Yeop Cha; Byung-Cheul Shin; Eui-Hyoung Hwang; Kristin Suhr; Mia Kim; In-Hyuk Ha (BMC Musculoskeletal Disorders, 2017)
Abstract Background Osteoarthritis (OA) and meniscal and ligament injuries of the knee are the two most common knee disorders in Korea. The aim of this study was to analyze the demographic characteristics, medical service use and related costs for these disorders, and the results are expected to help inform practitioners, researchers, and policy-makers. Methods The present study aimed to evaluate incidence and patient characteristics, and to assess current medical service use, usual care, and medical expenses of knee disorders by analyzing 2014 national patient sample data from the Korean Health Insurance Review and Assessment Service. Data was extracted using 3% stratified sampling from all Korea national health insurance claims submitted in 2014, and analyzed. Usual care for M17 knee osteoarthritis and S83 knee meniscal and ligament injury codes of the International Classification of Diseases, 10th revision (ICD-10) were determined by investigating total number of patients, sociodemographic characteristics, days in care, number of visits, and expenses. Results Knee OA showed the highest incidence in females aged ≥60 years, whereas meniscal and ligament injuries of the knee were most prevalent among patients aged <20 years and young adults. Total inpatient care expenses exceeded the cost of ambulatory care for both disorders. Ambulatory care was mainly provided at primary care clinics, with 90% of these visits made to orthopedic specialists. Medical expenses for knee OA and meniscal and ligament injuries were largely due to procedures/surgeries and injections, and procedures/surgeries and hospitalizations, respectively. Total replacement arthroplasty was the most commonly performed surgery for knee OA, while meniscectomy and cruciate ligament reconstruction were the most often performed surgeries for meniscal and ligament injuries. Intra-articular injection rates were 55% in knee OA patients and 3% in meniscal and ligament injury patients. Aceclofenac, diclofenac, and tramadol were the most frequently prescribed analgesics. Conclusions The current findings may be used as basic data for establishing medical policies and can benefit researchers and clinicians in recognizing trends and patterns of treatment for knee disorders.